2007
DOI: 10.1002/cncr.23182
|View full text |Cite
|
Sign up to set email alerts
|

Application of distance matrices to define associations between acute toxicities in colorectal cancer patients receiving chemotherapy

Abstract: We report on a new technique “using a partially inflated balloon through the atrial septal defect” to prevent prolapse of the left atrial disk of the Amplatzer septal occulder in large atrial septal defects (ASDs). Two patients underwent successful closure of their ASDs using this new technique. © 2011 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 25 publications
(19 reference statements)
3
47
1
5
Order By: Relevance
“…We found fatigue, nausea, intestinal disorders and hand-foot syndrome to be the most common symptoms reported by next of kin. This is confirmed by other studies investigating patients (Aprile et al, 2008;Berger et al, 2010;Goldberg et al, 2007;Griffin-Sobel, 2006;Hallquist Viale and Sommers, 2007;Henry et al, 2008;Kearney et al, 2008). However, the next of kin reported that nausea worsened with every treatment, whereas other studies on patients, in contradiction, have found that nausea decreases after every treatment (Henry et al, 2008;Kearney et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…We found fatigue, nausea, intestinal disorders and hand-foot syndrome to be the most common symptoms reported by next of kin. This is confirmed by other studies investigating patients (Aprile et al, 2008;Berger et al, 2010;Goldberg et al, 2007;Griffin-Sobel, 2006;Hallquist Viale and Sommers, 2007;Henry et al, 2008;Kearney et al, 2008). However, the next of kin reported that nausea worsened with every treatment, whereas other studies on patients, in contradiction, have found that nausea decreases after every treatment (Henry et al, 2008;Kearney et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…In a cohort of colorectal cancer patients, findings indicated the occurrence of localised (ulceration, abdominal pain, diarrhoea and malabsorption) as well as systemic (fatigue, nausea, infection and depression) toxicities in clusters. The recognition of concurrent occurrence of tissue-based and systemic toxicities has caused a shift in the potential applications of toxicity models to investigate regimen-related toxicity rather than tissuespecific toxicity [5]. Understanding toxicity clusters in response to different chemotherapy and/or radiotherapy regimens in different cancer types will aid in advancing mechanistic research and perhaps will also push forward the development of a systemic biomarker of toxicity.…”
Section: Links To Other Toxicitiesmentioning
confidence: 99%
“…Symptoms include pain, ulceration, nausea and vomiting, diarrhoea and rectal bleeding [3,4] and depend on the area affected. Systemic effects of oral and GI mucositis include fatigue, malnutrition, sepsis and occasionally death [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 has also been hypothesised to mediate chemotherapy-induced pain through central glial activation (9), with strong clinical evidence showing chemotherapy-induced gut toxicity is often paralleled by the symptom of pain (16,17). This is suggestive of common underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%